Extrinsic corrugation-assisted mechanical exfoliation of monolayer graphene - Pang, Shuping; Englert, Jan; Tsao, Hoi Nok; Hernandez, Yenny; Hirsch, Andreas; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2010)
An extrinsic corrugation-assisted mechanical exfoliation process is introduced to fabricate ultra-large, patterned monolayer graphene on silicon substrates. This exfoliation method, without any contamination, offers not only an ideal alternative for the scalable deposition of monolayer graphene on silicon substrates, but also provides a promising basis for the construction of graphene-based integrated circuits. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.